Bioprospecting and selection of growth-promoting bacteria for Cymbidium sp. orchids (Scientia Agricola, 2018)
Inoculants containing bacteria which promote growth in plants can increase productivity and both the economic and the environmental cost in plant crop systems. Similarly, in the flower and ornamental plant sector, the use of diazotrophic bacteria is a promising approach for improving orchid propagation from tissue culture to the ex vitro environment. We isolated diazotrophic bacteria from the roots and leaves of Cymbidium sp. The isolates were used to inoculate Cymbidium sp. plantlets during acclimatization in the nursery. After 150 days, plants were collected and their morphological and nutritional characteristics assessed. Eight bacterial strains were isolated containing traits that promote plant growth: Bacillus thuringiensis, Burkholderia cepacia, Burkholderia gladioli, Herbaspirillum frisingense, Pseudomonas stutzeri, Rhizobium cellulosilyticum, Rhizobium radiobacter, and Stenotrophomonas maltophilia. The isolated Herbaspirillum frisingense and Stenotrophomonas maltophilia increased 26 % and 29 % in dry matter in Cymbidium sp. plants, respectively, compared to the control. In addition, H. frisingense led to higher contents of N and P, by 68 % and 28 %, respectively, than those found in the control plants. These isolates, therefore, have potential for application as biostimulants and biofertilizers to promote growth and development of Cymbidium sp. during acclimatization.